issues in feedback learning - Abdullah, Rahman Bin (Advances in Social Sciences Research Journal, 2018)
Feedback learning is one of the major tools in educational programs improvisation and educational reforms. The complexity of feedback learning issues could not be understated, since many aspect of educational reforms and students improvisation rely on the feedback they received and given. There are many issues clouding the feedback learning and feedback giving process, which will be discussed over here. But, the debate eventually leads to betterment of the process and eventually acknowledging feedback learning as a very useful and productive tools either to the educational organization providing it or the students receiving it.